Removal of internal porosity in Supral 150 by hot isostatic pressing - Ahmed, Hamayun Kabeer (Cranfield University, 1985)
In recent years, considerable concern has been shown about the effects SPF cavitation has on the mechanical properties of superplastic alloys. This investigation was undertaken to ascertain whether Hot Isostatic Pressure (HIP) eliminated this cavitation in Supral 150 and correspondingly brought about an improvement in the mechanical properties. It was found that the density increased with various isothermal anneals; the activation energy for this process was close to that for grain boundary diffusion in aluminium (61.93 KJ mol-1). The rate of cavity sintering was seen experimentally to be enhanced by the application of pressures greater than 7 HPa, and had an activation energy of 62.42KJ mol-1. Complete cavity closure occurred when the external pressure was greater than the flow stress of the material at thaý temperature and strain-rate; the ratio of external pressure (Pe) to flow stress (of) increased with falling HIP temperature. The activation energy at constant strain-rate (Q-) associated with plastic flow under conditions of hole closure was found to be 53.54KJ mol-1; giving a corresponding activation energy at constant stress (Qa), which is close to that for lattice diffusion in aluminium. The alloy used contained a high level of hydrogen which caused blistering on heat treatment, and was also responsible for the reappearance of porosity in subsequently heat-treated material previously returned to theoretical density; the extent of which was decreased by the use of higher temperatures and pressures or by vacuum degassing the material prior to HIP. Post SPF room temperature ductility was enhanced by HIP. The scatter in the 0.2% PS and UTS values found in as-received SPF specimens was not altered by the use of low pressure HIP (up to 35 MPa), although higher pressures (100 NPa) did slightly enhance these values and drastically reduced the scatter. Room temperature fracture of as-received Supral was by a 450 ductile shear mechanism. In the SPF cavitated material, the external characteristics Of fracture had a more jagged appearance, as the cavitation alters the route of the propagating crack. SPF material which has been HIPped to remove cavitation, fails in a manner similar to the as-received material.